2017
DOI: 10.3390/app7070702
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Aging Resistance of Graphene Oxide Modified Asphalt

Abstract: Graphene oxide (GO) has a unique layered structure with excellent gas and liquid blocking properties. It is widely used in many areas, such as gas sensors, carbon-based electronics, impermeable membranes, and polymeric composite materials. In order to evaluate whether GO (1% and 3% by weight of asphalt) can improve the aging resistance performance of the asphalt, 80/100 penetration grade asphalt (90 A) and styrene-butadiene-styrene modified asphalt (SBS MA) were used to prepare the GO modified asphalt by the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…On the other hand, basing on Reference [17], it can be found that the thermal oxidative aging (85 °C for 240 h) can decrease the mechanical performance and healing levels of asphalt concrete obviously. Although the mechanism of thermal oxidative aging of asphalt material is not at all the same with UV aging, the effect tendency on the performance is somehow the same [18], so that UV aging may also cause a significant effect on the self-healing performance of asphalt concrete. In this research, the chemical functional groups of asphalt binder were tested by Fourier transform infrared spectrometer (FTIR).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, basing on Reference [17], it can be found that the thermal oxidative aging (85 °C for 240 h) can decrease the mechanical performance and healing levels of asphalt concrete obviously. Although the mechanism of thermal oxidative aging of asphalt material is not at all the same with UV aging, the effect tendency on the performance is somehow the same [18], so that UV aging may also cause a significant effect on the self-healing performance of asphalt concrete. In this research, the chemical functional groups of asphalt binder were tested by Fourier transform infrared spectrometer (FTIR).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the compatibility between asphalt and polymer also depended on the composition of the base asphalt. It was clear that the shape of the Cole-Cole plot for modified asphalt B was closer to symmetrical parabolas than that of modified asphalt A under the same SBS latex dosage [42,43,44]. This result showed that SBS latex-modified asphalt B had better compatibility than asphalt A, which is attributed to the composition differences of the base asphalt.…”
Section: Resultsmentioning
confidence: 88%
“…GO can promote the demulsification of oil in the water system; the demulsification efficiency was as high as 99.94% when the dosage of GO was about 30 mg/L [30,31]. GO can improve the high and low-temperature properties of asphalt and the aging resistance of asphalt [32,33]. In addition, GO can enhance the rutting resistance of asphalt [34].…”
Section: Introductionmentioning
confidence: 97%